2002
DOI: 10.4049/jimmunol.168.3.1172
|View full text |Cite
|
Sign up to set email alerts
|

Induction of MHC Class I Presentation of Exogenous Antigen by Dendritic Cells Is Controlled by CD4+ T Cells Engaging Class II Molecules in Cholesterol-Rich Domains

Abstract: We investigated interactions between CD4+ T cells and dendritic cells (DC) necessary for presentation of exogenous Ag by DC to CD8+ T cells. CD4+ T cells responding to their cognate Ag presented by MHC class II molecules of DC were necessary for induction of CD8+ T cell responses to MHC class I-associated Ag, but their ability to do so depended on the manner in which class II-peptide complexes were formed. DC derived from short-term mouse bone marrow culture efficiently took up Ag encapsulated in IgG FcR-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…In this context, the spore peptidoglycan cortex, with a unique muramic delta-lactam structural modification and the spore DNA are possible targets for PRR. A further explanation may lie in the fact that primed CD4 + T cells can license DC to cross-prime exogenous antigen through prolonged engagement and mutual stimulation through CD86 and CD40L [45] and macropinocytosis [46]. In support, we observed that B. subtilis spores induced a strong, IFN-c-dominated CD4 T cell response to exogenous spore proteins.…”
Section: Discussionsupporting
confidence: 73%
“…In this context, the spore peptidoglycan cortex, with a unique muramic delta-lactam structural modification and the spore DNA are possible targets for PRR. A further explanation may lie in the fact that primed CD4 + T cells can license DC to cross-prime exogenous antigen through prolonged engagement and mutual stimulation through CD86 and CD40L [45] and macropinocytosis [46]. In support, we observed that B. subtilis spores induced a strong, IFN-c-dominated CD4 T cell response to exogenous spore proteins.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, DC rafts have been shown to contain a subset of MHC class II-peptide complexes (24). Signals transmitted via DC rafts were shown to condition the DC for the activation of CD8 ϩ T cells (25). It is tempting to speculate that small GTPases likewise regulate the export of lipid rafts and of their components to the DC surface and thereby control phenotype and function of DCs.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…We, therefore, conducted experiments with LK-35.2 cells treated with anti-CD40 for varying lengths of time and fixed with paraformaldehyde before the addition of synthetic peptides. CD40 ligation enhanced the ability of APC to stimulate IL-2 release by T cell hybridomas specific for HEL 34 -45 or bovine RNase A [43][44][45][46][47][48][49][50][51][52][53][54][55][56] as early as 30 min after the addition of anti-CD40 (Fig. 2B, center and right).…”
Section: Cd40 Ligation-induced Enhancement Of the Ability Of Apc To Amentioning
confidence: 99%